The public-private sector wage differential for full-time male employees in Britain: a preliminary analysis - Chatterji, Monojit; Mumford, Karen (Bonn, 2007)
"Relative employment conditions have changed across the public and private sectors in Britain over the last decade with the former becoming a more attractive earnings option. Using new linked employee-employer data for Britain in 2004, this paper shows that, on average, full-time male public sector employees earn 11.7 log wage points more than their private sector counterparts. Decomposition analysis reveals that the majority of this pay premium is associated with public sector employees having individual characteristics associated with higher pay and to their working in higher paid occupations. Whilst there is some evidence of workplace segregation in the private sector, there is little indication that rates of return vary across the earnings distribution for either public or private sector employees. It no longer appears to be the case that the public sector provides a refuge for the low skilled at the expense of the highly educated. Furthermore, working conditions appear more uniform in the public sector and, unlike the private sector, there is no significant penalty associated with ethnic background."